Morphological, Agronomical Changes and Oil Content in Purslane (Portulaca oleracea L.) under Drought Stress and Biological / Chemical Fertilizer of Nitrogen - M Inanloofar; H Omidi; AR Pazoki (Institue of Medicinal Plants, ACECR, 2013)
Background: Purslane is a valuable medicinal plant and study of quantity yield and phytochemical changes of them in drought is necessary. Objective: Determining the effects of nitrogen chemical and biofertilizers on quantity yield and oil content of purslane herb under drought stress and feasibility of replacing chemical fertilizers with biological fertilizers. Methods: This experiment was done in the Research farm of Shahed University in 2012 on the base of split-plot experiment in a randomized complete block design (RCBD) with three replications. The irrigation as main factor in levels of 50±3 mm, 100±3 mm and 150±3 mm of evaporation pan and also application of nitrogen fertilizers as subsidiary factor in levels including control (without fertilizer use), about 250 kg/ha fertilizer of urea, incorporation of about 2.5 L/ha of biological fertilizer with 120 kg/ha of chemical fertilizers nitrogen about 2.5 L/ha and biological fertilizer of nitrogen about 5 L/ha were considered. Results: The treatments of drought and fertilizers had significant effects on plant height, fresh weight of leaf, stem, total fresh weight, dry weight of leaf, stem, total dry weight, grain yield, relative water content (RWC), oil content of grain and oil yield (p≤0.01). The highest quality and quantity yield of purslane were obtained on combined treatments of fertilizer and optimal irrigation (3 ± 50) mm evaporation and also the smallest amount of quality and quantity yield of purslane was achieve at control treatment and Severe stress (3 ± 150) ml m evaporation pan. Conjunctive use of bio-fertilizer and chemical treatments under optimum irrigation treatment was increased the oil content about 23% compared to the control. Conclusion: Drought was reduced yield and seed oil content purslane. Conjunctive use of nitrogen bio-fertilizers (NitroxinR) with chemical urea increased yield and quality of Purslane plant. Therefore, the biofertilizers can be an alternative to replacing chemical fertilizers for increasing Purslane production which is in order to minimize of environmental pollution.